Comportamento de compra infantil: um estudo sobre os elementos de persuasão presentes nas embalagens de salgadinhos - Santos, Nataluan de Carvalho (2018)
The industrialization of food has influenced eating habits and buying behavior. In this context, it is observed the participation of the child consumer and the purchase stimulus strategies promoted by the product packaging. From this understanding, this work sought to analyze the elements of persuasion present in the packaging of infant snacks that influence infant consumers during the purchase process. For this purpose, an exploratory and qualitative research was carried out on nine packs of saltine from Iane, São Braz and Semalo. The present study was based on the concepts of consumer behavior (KOTLER; KELLER, 2012; BASTA et. al., 2011; HOYER; MACLNNIS, 2011; PATRIOTA; FARIAS, 2013) and marketing stimuli through packaging (KAPFERER, 2008; SARANTÓPOULOS et al., 2010; BASTA et. al., 2011; COUTINHO; LUCIAN, 2015; YOSHIHARA; CASSIANO, 2010; FRUGÉRIO; KAETSU, 2015; NAOMI KLEIN, 2009). Through the analysis of content the categories were identified product name; colors used, stamped images and information offered. We have noticed that colors as well as contribute to the design, evidence the information contained in the packaging and attract attention by promoting experience for consumers. With regard to the printed images we find that they generate meanings and influence the sensations of consumers related to the acceptance, purchase and use of the product. In addition to these, we find that the brand and the information also influence the purchasing process. Finally, the results of the research indicate that the persuasive elements of the packages analyzed serve to stimulate consumption, thus demonstrating the attractive power of the packages.